Conhecimento, atitudes e práticas relacionadas à DST/AIDS - Chicrala, M.A.; Barros, C.R.P.; Cromack, L.M.F.; Meirelles, Z.V.; Silva, M.R.N.; Baket, G. (Brazilian Journal of Sexually Transmitted Diseases, 1997)
Introduction.-ln Brazil, 32,9% of the accumulated cases of SIDA until june 30’h were found between 20 and 30 years of age. lt is probable that the contamination has accured during adolescence, because of the large period of latency of the disease. Goals.-To identify knowledges and beltavior conected to STD/SIDA and to evaluate the interest of adolescents to receive additional information. Methodology.-Data were collected from a questionnaire specialy developed to this study. The questionnaire is constituted by quescions about knowledge and behavior concerning to STD/SJDA. Adolescents were interviewed individually by Ambulatório Avançado team, during consulting time. Results.-169 adolescents were in terviewed, 142 (84%) female and 27 (16%) male. 92,9% had already heard aboul STD. The most mentioned: SIDA (95,5 %) , gonorrhea (51, 6%) and syphilis (35, 7%). 78, 7% recognize at /east one way of transmission of STD. The mosr mentioned were: sexual via (97.7%), blood via (17,3%) and drug abuse (12,8%). 52,1 % of adolescents was sexually active, from whom 50% do something against STD transmission in their own lives and 39,8% use condoms. 98,8% of interviewed had already heard about SIDA, which is more frequently associated to a non curable disease. 90,5% know how it is transmited. The most mentioned forms: sexual via (94, 1%), blood via (70,6%) and contamined syringes (41 ,2%). 51 ,1% of adolescents do something not to catch the disease and 36,4% wld that use condoms. Conclusion.-The main source of information for teens is school (54,1%) and Ambulatório Avançado (51,6%). Levei of knowledge is high: 92,9% had already heard about STD and 98,8% about SIDA. 90,5% said that know how SIDA is transmited and 78,8% lww STD are transmited. The levei of condom use is low, comparing to high levei of knowledge. Despite the high levei of knowledge, adolescents wanted to receive additional information about STD/ SIDA.